A new polyoxygenated flavonol gossypetin-3-O-β-d-robinobioside from Caesalpinia gilliesii (Hook.) D. Dietr. and in vivo hepatoprotective, anti-inflammatory, and anti-ulcer activities of the leaf methanol extract - Emam, Mahmoud; El Raey, Mohamed A.; El-Haddad, Alaadin E.; El Awdan, Sally A.; Rabie, Abdel-Gawad M.; El-Ansari, Mohamed A.; Sobeh, Mansour; Osman, Samir M.; Wink, Michael (Molecules, 2018)
A hitherto unknown polyoxygenated flavonol robinobioside (gossypetin-3-O-β-d-robinobioside) was isolated from the leaves of Caesalpinia gilliesii along with thirteen known phenolic secondary metabolites. The isolated compounds were characterized using spectroscopic analysis, including 1D and 2D NMR and mass spectrometry (MS) analyses. The extract reduced the level of liver damage in CCl4-induced liver injury in rats. A decrease of the liver biomarkers—aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and an increase of total antioxidant capacity (TAC) levels—were observed similar to the liver protecting drug silymarin. In addition, the extract showed promising activity against carrageenan-induced paw edema in rats and protected their stomachs against ethanol-induced gastric ulcers in a concentration dependent fashion. The observed activities could be attributed to the high content of antioxidant polyphenols. Our results suggest that the C. gilliesii has the capacity to scavenge free radicals and can protect against oxidative stress, and liver and stomach injury.